Sins of the Black Flamingo - Wheeler, Andrew, 1976-; Wheeler, Andrew, 1976-; Moore, Travis (Image Comics, Inc., 2023)
"Sebastian Harlow is The Black Flamingo, a flamboyant and narcissistic thief who gets kicks stealing mystic artifacts from the wealthy and corrupt of Miami's occult underground. When his latest job leads Sebastian to his biggest score so far, the hedonistic outlaw finds not just all manner of villains and monsters hot on his trail, but something he never expected to discover: something to believe in."--Back cover.